2021
DOI: 10.1002/jlb.3a0321-175r
|View full text |Cite
|
Sign up to set email alerts
|

Hemin-primed dendritic cells suppress allergic airway inflammation through releasing extracellular vesicles

Abstract: Hemin, a substrate of heme oxygenase (HO)-1, induces HO-1 expression on a variety of cells to exert anti-oxidant and anti-inflammatory roles. However, the role of HO-1 in allergic diseases for dendritic cells (DCs) is not fully understood. Here, we report that HO-1 modulates asthmatic airway inflammation by hemin-treated DC-released extracellular vesicles (DCEVs). Following induction of bone marrow-derived DCs by hemin and then by house dust mite (HDM) in vitro, mouse CD4+ naïve T cells were cocultured with DC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Anti-F4/80 treatment of OVA-induced asthmatic mice inhibited alternately activated macrophages and also attenuated Th2 cell response in lung tissue [ 70 ]. Similarly, reducing the levels of IL-4, IL-5, and IL-13 in the lung and the number of Th2 cells in mediastinal lymph nodes, while increasing the number of Treg cells in mediastinal lymph nodes, can alleviate allergic airway inflammation [ 71 ]. Acupuncture also seems to reduce airway inflammation and airway hyperreactivity (AHR) in asthmatic patients by correcting the imbalance of CD4 + T lymphocyte subsets (Th1/Th2 and Treg/Th17) [ 72 ].…”
Section: Cd4 + T Cells In Lung Homeostasismentioning
confidence: 99%
“…Anti-F4/80 treatment of OVA-induced asthmatic mice inhibited alternately activated macrophages and also attenuated Th2 cell response in lung tissue [ 70 ]. Similarly, reducing the levels of IL-4, IL-5, and IL-13 in the lung and the number of Th2 cells in mediastinal lymph nodes, while increasing the number of Treg cells in mediastinal lymph nodes, can alleviate allergic airway inflammation [ 71 ]. Acupuncture also seems to reduce airway inflammation and airway hyperreactivity (AHR) in asthmatic patients by correcting the imbalance of CD4 + T lymphocyte subsets (Th1/Th2 and Treg/Th17) [ 72 ].…”
Section: Cd4 + T Cells In Lung Homeostasismentioning
confidence: 99%
“…Based on these effects, when Hem treated DC-derived treated EVs (Hem-EV) were administered via inhalation to a house dust mite (HDM) induced asthmatic mouse model, it reduced eosinophil infiltration and mucus secretion in the airways, decreased the levels of IL-4, IL-5, and IL-13 in the lungs, and reduced the Th2 cells number in the mediastinal lymph nodes (MLNs), while increasing the number of regulatory T (Treg) cells in the MLNs. These immune-regulatory effects are believed to be attributed to the regulation of HO-1 expression in Hem-EVs [ 81 ]. The resveratrol (Res), a well-known antioxidant compound and non-flavonoid polyphenol, was successfully loaded into EV derived from primary microglia.…”
Section: Engineering Methods Of Ev and Applications For Regenerative ...mentioning
confidence: 99%
“… Target cell Treatment material Concentration Ref. 1 RAW 264.7 Gemfibrozil 100 μg/ml [ 77 ] 2 RAW 264.7 Silibinin 50 μg/ml [ 78 ] 3 RAW 264.7 Edaravone 87.5 μg/ml [ 79 ] 4 SMC Cystatin C 1.95 μg/ml [ 80 ] 5 Dendritic cell Hemin 4.89 μg/ml [ 81 ] 6 Primary microglia and neurons Resveratrol 9.13 μg/ml [ 17 ] 7 BMSC TGFβ3 50 ng/ml [ 15 ] 8 BMSC Erythropoietin (EPO) 0.84 μg/ml [ 82 ] 9 BMSC tauroursodeoxycholic acid (TUDCA) 1.3 mg/ml [ 95 ] 10 BMSC Dimethyloxaloylglycine (DMOG) 0.17 mg/ml [ 96 ] 11 UCMSC Tanshinone IIA 2.94 μg/ml [ 85 ] 12 UCMSC Melatonin 4.65 μg/ml [ 16 ] 13 ADMSC Melatonin 4.65 μg/ml [ 87 ] ...…”
Section: Engineering Methods Of Ev and Applications For Regenerative ...mentioning
confidence: 99%
“…Notably, it has been reported that many conventional DCs(cDCs) are located in the mucous membranes of the airway ducts ( 107 109 ). These cells extend pseudopods between epithelial cells to capture antigens present within the airway cavity ( 102 , 110 , 111 ). Based on their functional differences, cDCs are further categorized into two subsets: cDC1 and cDC2.…”
Section: The Phenotype Of Heterogeneous DC Subsets Of the Lungmentioning
confidence: 99%